A Descriptive Qualitative Research on Figurative Language on Adele’s Album: 30 and Avril Lavigne’s Album: The Best Damn Thing - Kertayasa, I Wayan; Utami, Ni Made Verayanti; Tustiawati, Ida Ayu Mela (Austronesian: Journal of Language Science & Literature, 2025)
This study analyzes the use of figurative language in Adele’s album 30 and Avril Lavigne’s album The Best Damn Thing. The objectives of this study are: (1) to identify the types of figurative language found in each song of both albums, and (2) to analyze the most dominantly used figurative language in each album and interpret its meaning. This research employs a descriptive qualitative method, using all songs from the two albums as data sources. The findings reveal that Adele’s 30 features eight types of figurative language: simile, metaphor, personification, metonymy, symbol, paradox, hyperbole, and understatement. In contrast, Avril Lavigne’s The Best Damn Thing contains four types: simile, metaphor, personification, and hyperbole. Hyperbole emerges as the most dominantly used figurative language in both albums. These findings suggest that hyperbolic expressions play a central role in conveying emotional intensity and artistic expression in contemporary pop music.